Estudio de factibilidad para la creación de una empresa dedicada a la asesoría, acompañamiento en siniestros, y comercialización del seguro obligatorio de accidentes de tránsito, SOAT, en la ciudad de Armenia-Quindío. (2014)
The consultancy and accompaniment in SOAT is a need that has omitted on the part of those who commercialize insurances, since big companies variety they devote themselves to sell the SOAT as a product of obligatory fulfillment for owners of vehicles, cars and motorbikes that it continues in increase in the last years, leaving in doubt the consultancy and the accompaniment in the occurrence of catastrophes, lines of attention, between other aspects, what has generated the opportunity for the creation of a company that devotes itself to the consultancy, accompaniment and that the SOAT commercializes in insurances packages. During the achievement of the survey applied in the city of Armenia like source of compilation of the information, there was widespread acceptance of the business idea that tries to be implemented, an unsatisfied need as for the accompaniment and consultancy in insurances, and the intensity of acquisition of the packages of insurances in accordance with the profiles of the clients. Across the practicality study there is realized an investigation that contemplates the aspects for the starting of the managerial initiative, identifying the potential market, the aspects necessary for the adequacy of the plant, the location, the legal aspects and the financial aspects that throw positive results in the financial and warning conditions, with utilities considered top to the hundred annual millions in the first year of functioning achieved by the commercialization of THREE THOUSAND SIX HUNDRED annual insurance packages.